2011
DOI: 10.1166/jnn.2011.3663
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Detection of DNA Hybridization Using Pyrene-Functionalized Single-Walled Carbon Nanotubes: Effect of Chemical Structures of Pyrene Molecules on DNA Sensing Performance

Abstract: We investigate the effect of functional groups of pyrene molecules on the electrical sensing performance of single-walled carbon nanotubes (SWNTs) based DNA biosensor, in which pyrenes with three different functional groups of carboxylic acid (Py-COOH), aldehyde (Py-CHO) and amine (Py-NH2) are used as linker molecules to immobilize DNA on the SWNT films. UV/Visible absorption spectra results show that all of the pyrene molecules are successfully immobilized on the SWNT surface via pi-pi stacking interaction. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The linker molecules were also characterised using absorbance spectra, which could easily resolve a concentration level of 0.2 µg/mL, as shown in Figure 7. The data show clear triple peaks in absorbance due to the pyrene moiety that is central to the Pyr-NHS ester linker molecules, also observed by, Baek et al (2011) after functionalising carbon nanotubes for electrical detection of DNA hybridisation. The data in Figure 7 also show a repeat measurement (off-set for clarity) of the absorbance spectra over the 220-400 nm wavelength range, demonstrating excellent repeatability of the measurements.…”
Section: Functionalisation Of Gfetssupporting
confidence: 56%
“…The linker molecules were also characterised using absorbance spectra, which could easily resolve a concentration level of 0.2 µg/mL, as shown in Figure 7. The data show clear triple peaks in absorbance due to the pyrene moiety that is central to the Pyr-NHS ester linker molecules, also observed by, Baek et al (2011) after functionalising carbon nanotubes for electrical detection of DNA hybridisation. The data in Figure 7 also show a repeat measurement (off-set for clarity) of the absorbance spectra over the 220-400 nm wavelength range, demonstrating excellent repeatability of the measurements.…”
Section: Functionalisation Of Gfetssupporting
confidence: 56%
“…They confirmed the adhesion of the high aromatic system on the graphene surface by electrochemical measurement, and confirmed by controlled experiments that the irreversible adhesion of the high aromatic system on the graphene surface was formed by the non-covalent manner of the πstacking of the aromatic ring. Both Hongjie Dai et al [49] and Baek et al [50] also found the similar strong interact on the surface of carbon nanotubes. Since the product has more benzene rings in the NDI and the branch, the benzene ring can interact with the carbon six-membered ring of the carbon material to attach the product to the EG (SWNT).…”
Section: Uv-vis @ CDmentioning
confidence: 74%
“…The biosensor described efficiently discriminated a complementary and a mismatch-containing targets. Baek et al studied the effect of the structure of the pyrene anchor on the biosensor performance [ 258 ]. Three types of pyrene derivatives (1-pyrenebutanoic acid, 1-pyrene carboxaldehyde, and 1-pyrenyl methylamine) were adsorbed on SWCNT films and reacted with oligonucleotides in specific conditions (carboxylic group activation, Schiff’s base reaction, followed by the reduction of amide, and UV-crosslinking, respectively) ( Figure 39 ).…”
Section: Supramolecular Assembliesmentioning
confidence: 99%